2021
DOI: 10.1126/sciadv.abc0444
|View full text |Cite
|
Sign up to set email alerts
|

A pebble accretion model for the formation of the terrestrial planets in the Solar System

Abstract: Pebbles of millimeter sizes are abundant in protoplanetary discs around young stars. Chondrules inside primitive meteorites—formed by melting of dust aggregate pebbles or in impacts between planetesimals—have similar sizes. The role of pebble accretion for terrestrial planet formation is nevertheless unclear. Here, we present a model where inward-drifting pebbles feed the growth of terrestrial planets. The masses and orbits of Venus, Earth, Theia (which later collided with Earth to form the Moon), and Mars are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 74 publications
7
126
2
Order By: Relevance
“…5C ). Thus, contrary to some recent studies ( 7 , 9 , 10 ), we conclude that the terrestrial planets could not have formed by accretion of large masses (~40%) of CC pebbles from the outer solar system. Instead, the terrestrial planets could only have formed by pebble accretion if the vast majority of the pebbles had an NC isotopic composition.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…5C ). Thus, contrary to some recent studies ( 7 , 9 , 10 ), we conclude that the terrestrial planets could not have formed by accretion of large masses (~40%) of CC pebbles from the outer solar system. Instead, the terrestrial planets could only have formed by pebble accretion if the vast majority of the pebbles had an NC isotopic composition.…”
Section: Discussioncontrasting
confidence: 99%
“…Instead, the terrestrial planets could only have formed by pebble accretion if the vast majority of the pebbles had an NC isotopic composition. To this end, it has been suggested that CC material initially resided far from the Sun and that it reached the terrestrial planet region by radial drift only after some time t , before which the planets grew by accreting NC pebbles ( 7 ). Within this framework, the fraction of CC material in the terrestrial planets would be higher the earlier the change in pebble composition from NC to CC in the terrestrial planet region would have occurred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the models of Brouwers & Ormel (2020) the pebbles evaporating in the planetary atmosphere do not allow such a fast transition into runaway gas accretion, while the study of Ormel et al (2021) shows that envelope pollution significantly reduces the time at which the planet reaches the cross over mass for runaway gas accretion in line with Venturini et al (2015). Furthermore, Johansen et al (2021) shows that water-rich pebbles entering the planetary Hill sphere can evaporate high up in the planetary atmosphere, where recycling flows (Lambrechts & Lega 2017;Cimerman et al 2017) could transport the water vapor away from the planet, preventing the buildup of a high Z envelope.…”
Section: Gas Accretionmentioning
confidence: 99%